Nocturnal Bee Pollinators Are Attracted to Guarana Flowers by Their Scents - Krug, Cristiane (Front Plant Sci, 2018)
Floral scent is an important component of the trait repertoire of flowering plants, which is used to attract and manipulate pollinators. Despite advances during the last decades about the chemicals released by flowers, there is still a large gap in our understanding of chemical communication between flowering plants and their pollinators. We analyzed floral scents of guarana (Paullinia cupana, Sapindaceae), an economically important plant of the Amazon, using chemical analytical approaches, and determined the attractiveness of the scent to its nocturnal bee pollinators using behavioral assays in the field. Pollen loads of attracted bees were also analyzed. Inflorescences of guarana emit strong scents, both during day and at night, with some semi-quantitative differences between day- and night-time scents. Synthetic scent mixtures containing some of the identified floral scent components, including the most abundant ones, i.e., linalool and (E)-β-ocimene, successfully attracted the nocturnal Megalopta bee pollinators. Pollen analyses revealed that many of the attracted bees had pollen grains from previous visits to guarana flowers on their bodies. Overall, our data show that guarana flowers attract nocturnal bee visitors by their strong scents and suggest that the chemical communication between this plant and its pollinators is a key component in crop production of this economically important plant species.